PBPK-PD modeling for the preclinical development and clinical translation of tau antibodies for Alzheimer’s disease - Bloomingdale, Peter; Bumbaca-Yadav, Daniela; Sugam, Jonathan; Grauer, Steve; Smith, Brad; Antonenko, Svetlana; Judo, Michael; Azadi, Glareh; Yee, Ka Lai (Frontiers in Pharmacology, 2022)
Disrupted tau proteostasis and transneuronal spread is a pathological hallmark of Alzheimer’s disease. Neurodegenerative diseases remain an unmet medical need and novel disease modifying therapeutics are paramount. A physiologically-based pharmacokinetic-pharmacodynamic (PBPK-PD) modeling approach was employed to support the preclinical development and clinical translation of therapeutic antibodies targeting tau for the treatment of Alzheimer’s disease. PBPK-PD modeling enabled a quantitative understanding for the relationship between dose, affinity, and target engagement, which supported lead candidate optimization and predictions of clinically efficacious dosing regimens.